Case report: p.Glu134del SOD1 mutation in two apparently unrelated ALS patients with mirrored phenotype - Gianferrari, Giulia; Martinelli, Ilaria; Simonini, Cecilia; Zucchi, Elisabetta; Fini, Nicola; Carra, Serena; Moglia, Cristina; Mandrioli, Jessica (Frontiers in Neurology, 2023)
With upcoming personalized approaches based on genetics, it is important to report new mutations in amyotrophic lateral sclerosis (ALS) genes in order to understand their pathogenicity and possible patient responses to specific therapies. SOD1 mutations are the second most frequent genetic cause of ALS in European populations. Here, we describe two seemingly unrelated Italian patients with ALS carrying the same SOD1 heterozygous c.400_402 deletion (p.Glu134del). Both patients had spinal onset in their lower limbs, progressive muscular weakness with respiratory involvement, sparing bulbar function. In addition to the clinical picture, we discuss the possible pathogenic role of this unfamiliar SOD1 mutation.